THE REQUIREMENTS TO UKRAINE’S HIGHER EDUCATION IN THE CONTEXT OF INNOVATIVE AND INFORMATIONAL SOCIETY’S FORMATION - Кісіль, М. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article investigates basic requirements to Ukraine’s higher education in the context of Innovative and Informational Society’s Formation.